Endocannabinoid Signaling in Embryonic Neuronal Motility and Cell–Cell Contact – Role of mGluR5 and TRPC3 Channels. (1st April 2018) - Turunen, Pauli M.; Louhivuori, Lauri M.; Louhivuori, Verna; Kukkonen, Jyrki P.; Åkerman, Karl E.
Highlights: 2-AG promotes neuroblast movement and reduces contacts between migrating neuroblasts. Neuroblast movement is enhanced by inhibiting mGluR5 or TRPC3. Blocking 2-AG production reversed this effect. Endocannabinoid system and mGluR5/TRPC3 system have a functional connection. 2-AG-induced motility is also affected with neuregulin signaling. Abstract: Cell–cell communication plays a central role in the guidance of migrating neuronal precursor cells during the development of the cerebral cortex. Endocannabinoids (eCBs) have previously been shown to be one of the central factors regulating neuronal migration. In this study the effects of eCBs on different parameters, expected to affect embryonic cortical neuronal motility have been analyzed in neurosphere-derived neuroblasts using time-lapse microscopy. Increased endogenous production of the endocannabinoid 2-arachidonyl glycerol (2-AG) causes bursts of neuroblast motility. The neuroblasts move longer distances and show a low frequency of turning, and the number of neuron–neuron contacts are reduced. Similar changes occur interfering with the function of the metabotropic glutamate receptor 5 (mGluR5) or its transducer canonical transient receptor potential channel 3 (TRPC3) or the neuregulin receptor ErbB4. Blocking of 2-AG production reverses these effects. The data suggest that eCB-regulated neuronal motility is controlled by mGluR5/TRPC3 activity possibly via NRG/ErbB4 signaling.